Investor Protection and Real Investment by U.S. Multinationals - Kelley, Eric; Woidtke, Tracie (Journal of Financial and Quantitative Analysis, 2006)
Abstract In spite of the growing research concerning investor protection, the relation between investor protection and real investment by foreign multinationals is largely unexplored. Recognizing this relation, however, is especially important in light of the surge in cross-border activity in recent decades and the potential impact cross-border investment can have on a country's economic development. We find that U.S. multinational foreign investment is significantly greater both when shareholder protection is poor and when creditor protection is poor. Consistent with existing literature, our results suggest that U.S. firms have greater comparative advantages when local firms in poor investor protection countries either i) invest suboptimally due to agency problems or ii) have constrained access to debt capital. The increased investment by U.S. multinationals in poor investor protection countries is of particular interest, because it suggests an important way in which adverse outcomes related to poor investor protection may be mitigated.